2019
DOI: 10.1126/sciadv.aav9839
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular dialkylation of alkenes with two distinct C(sp 3 )─H bonds enabled by synergistic photoredox catalysis and iron catalysis

Abstract: The functionalization of unactivated C(sp3)─H bonds represents one of the most powerful and most atom-economical tools for the formation of new carbon-based chemical bonds in synthesis. Although cross-dehydrogenative coupling reactions of two distinct C─H bonds for the formation of carbon-carbon bonds have been well investigated, controlled functionalizations of two or more different C(sp3)─H bonds across a functional group or a molecule (e.g., an alkene or alkyne) in a single reaction remain challenging. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(43 citation statements)
references
References 46 publications
(99 reference statements)
0
43
0
Order By: Relevance
“…Focus will be done on transition metals most used in combination with photocatalysis, id est : palladium, nickel, gold and copper. Indeed, other metals have also been used in metallaphotocatalysis such as Co, Ru or Rh which have been previously reviewed in the same aim iron has also been studied . This review gathers, to the best of our knowledge, all the new advances made in dual photoredox/transition‐metal catalysis until mid‐2019 and updates the previous key review in this field, reported by MacMillan and co‐workers in 2017 .…”
Section: Introductionmentioning
confidence: 59%
“…Focus will be done on transition metals most used in combination with photocatalysis, id est : palladium, nickel, gold and copper. Indeed, other metals have also been used in metallaphotocatalysis such as Co, Ru or Rh which have been previously reviewed in the same aim iron has also been studied . This review gathers, to the best of our knowledge, all the new advances made in dual photoredox/transition‐metal catalysis until mid‐2019 and updates the previous key review in this field, reported by MacMillan and co‐workers in 2017 .…”
Section: Introductionmentioning
confidence: 59%
“…The group of Song and Li reported a dual catalytic system for the intermolecular dialkylation of alkenes with common alkanes and 1,3‐dicarbonyl compounds via synergistic photoredox catalysis and iron catalysis (Scheme 2). [8] This method represents a powerful strategy for the construction of functionalized 1,3‐dicarbonyl compounds through the controlled functionalization of two or more different C(sp 3 )−H bonds, which features high atom economy, broad substrate scope, and excellent functional group tolerance. Mechanistic studies suggest that the reaction is triggered by the generation of the tert ‐butoxyl radical t BuO .…”
Section: Cooperative Iron/photoredox Dual Catalysismentioning
confidence: 99%
“…The group of Song and Li has shown that Fe(OTf) 2 and Eosin Y could be combined to catalyze the multi‐component assembly of alkenes 3 , alkanes 71 and 1,3‐dicarbonyl compounds 72 (Scheme 30). [51] …”
Section: Organo‐/iron Catalysismentioning
confidence: 99%
“…The group of Song and Li has shown that Fe(OTf) 2 and Eosin Yc ould be combined to catalyzet he multi-component assembly of alkenes 3,a lkanes 71 and 1,3-dicarbonyl compounds 72 (Scheme 30). [51] This transformation features ac omplex merged-relay catalytic sequence. The photoredox organocatalyst ensures formation of the alkyl radical by reactingw itht he peroxide oxidant while also triggering the oxidation of the iron(II) complex.The generated iron(III) can then react with the formed alkyl radical generating ac arbocation, subsequently trapped by the nucleophile.…”
Section: A Achiral and Racemic Reactionsmentioning
confidence: 99%